Excellence in health care in the next millennium: South African realities and challenges - Marie Muller (AOSIS, 1998)
This paper was delivered at an international conference as the closing address with the topic "Excellence in health care in the next millennium." Due to the length of the presentation, it is divided into two articles. Opsomming Hierdie referaat was by 'n internasionale kongres as die afsluitingsreferaat gelewer met die titel "Excellence in health care in the next millennium." Weens die lengte van die referaat, word dit in twee artikels verdeel. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.